Pembuatan Panel Automatic Transfer Switch – Automatic Main Failure (ATS – AMF) di PT. Tiga Kreasi Indonesia - Alamsyah Alamsyah; Ilham Akbar Darmawan (Asosiasi Riset Ilmu Teknik Indonesia, 2024)
The rapid development of technology will obtain excellent effectiveness and efficiency from sources of electrical energy owned by a company or agency. With the progress of the industrial world today, the development of digital technology which ends in computer systems indirectly makes control technology involved as part of this progress. The availability of a power source is a very important aspect in the midst of technological developments. However, because the system is very complex, starting from the power plant to distribution to consumers, there is a high possibility of disturbances that can cause the flow of electrical energy to consumers to be cut off. There are certain places including factories, offices, banks, campuses, hospitals, airports and other places that could potentially endanger one's safety or drastically disrupt the course of the economic cycle. The flow of electrical energy must not be interrupted for a very long time because it can hamper the production process. and others, so that additional supply is needed to anticipate when the electricity is cut off from the National Power Plant source.